(3NWQI GdWja aj QMdI GdTJGA hGdUjas - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3fMeO Gddg MeO eYJQa HMbg hfbhd(B: (3hbGFdI(B: (3Ua dj aOjJc (B- (3QMdI YfjJ HgG, jG TbI GdbdH, ef HYO abdJ NPjgG ef dSGf HdGZI ceG fXe GdjGbhJ hGdOQ aj YbO s
(3BNQgG (B:s
(3gfG GfJgi GdJbjjO hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B50 - (3U(B68s
(3GfXQgG eY QSGdI GdUGMH Hf YHGO aj cTa YjhH GdeJfHjs
(3fSNI Yf fSNI CNQi ocJHJ SfI (B748(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B288 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs